Enterovirus 71 in Malaysia: A decade later - Chan, Yoke Fun; Sam, I.C.; Wee, K.L.; AbuBakar, Sazaly (2011)
In the last decade, Malaysia has experienced several hand, foot and mouth disease (HFMD) epidemics, complicated by fatalities due to severe neurological involvement. Enterovirus 71 (EV-71) has been implicated as the major causative agent for these epidemics. EV-71 infection is a global public health problem with pandemic potential. In many parts of Asia-Pacific, the virus has emerged as one of the most deadly virus infections amongst young children. The virus is highly transmissible through faecal-oral route and respiratory droplets. A recent rise in neurological complications and deaths suggests that the viruses currently circulating may be more virulent. The major risk factor associated with more severe EV-71 infection is young age and poor cellular immunity. Rapid laboratory diagnosis and molecular surveillance is important to closely monitor the emergence of new EV-71 subgenotypes. Since vaccine and anti-virals for EV-71 are not available, control and prevention strategies remain the only ways to combat the infection.